The substitutability of non-fossil energy, potential carbon emission reduction and energy shadow prices in China. (August 2017) - Xie, Hualin; Yu, Yanni; Wang, Wei; Liu, Yanchu
Abstract: The rapidly increasing consumption of energy and fossil fuel dominated energy structure have caused great pressure on energy security and carbon reduction policies in China, and the Chinese government has attempted to substitute fossil with non-fossil energy. To investigate the feasibility of replacing fossil energy with non-fossil energy in China, we apply an input distance function to estimate the substitutability of non-fossil energy for fossil energy and compare shadow prices. The result confirms the feasibility of substituting non-fossil energy for fossil energy. We then divide the non-fossil energy into nuclear energy and renewable energy and find that nuclear energy is more suitable than renewable energy to substitute for fossil energy. The shadow price ratio of non-fossil to fossil energy is 268.41 on average in the study period. The ratio experiences several fluctuations and shows a declining trend at the end of the study period, implying that improving energy structure in China is very promising. Highlights: This study confirms the feasibility of substituting non-fossil energy for fossil energy. Nuclear energy is more suitable for replacing fossil energy than renewable energy. The shadow prices of fossil energy and non-fossil energy are calculated and compared. Policy implications to develop non-fossil energy vigorously in China are proposed.